2011
DOI: 10.1371/journal.pone.0018439
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role for Shed Soluble Major Histocompatibility Class I Molecules as Modulators of Neurite Outgrowth

Abstract: The neurobiological activities of classical major histocompatibility class I (MHCI) molecules are just beginning to be explored. To further examine MHCI's actions during the formation of neuronal connections, we cultured embryonic mouse retina explants a short distance from wildtype thalamic explants, or thalami from transgenic mice (termed “NSE-Db”) whose neurons express higher levels of MHCI. While retina neurites extended to form connections with wildtype thalami, we were surprised to find that retina neuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…We previously showed that recombinant self- (but not non-self) MHCI monomers, as well as soluble MHCI that was shed from neurons, could inhibit overall neurite outgrowth from cultured retina explants (Escande-Beillard et al, 2010; Washburn et al, 2011). To further analyze the effects of these closed MHCI conformers on neurite outgrowth we incubated wildtype E15 hippocampal cultures with a self-MHCI monomer, or a non-self MHCI monomer (200 pM) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that recombinant self- (but not non-self) MHCI monomers, as well as soluble MHCI that was shed from neurons, could inhibit overall neurite outgrowth from cultured retina explants (Escande-Beillard et al, 2010; Washburn et al, 2011). To further analyze the effects of these closed MHCI conformers on neurite outgrowth we incubated wildtype E15 hippocampal cultures with a self-MHCI monomer, or a non-self MHCI monomer (200 pM) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed that low levels of recombinant self-MHCI monomers, or soluble MHCI that was shed from neurons, inhibited neurite outgrowth from cultured embryonic retinas (Escande-Beillard et al, 2010; Washburn et al, 2011). Based on this, we anticipated that genetically reduced neuronal MHCI expression would promote neuritogenesis, while genetically increased neuronal MHCI expression would inhibit neuritogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although MHC class I is best-known for its role in adaptive immunity, MHC class I also has important roles in the normal, healthy developing and adult brain (e.g., Huh et al 2000;Loconto et al 2003;Leinders-Zufall et al 2004;Goddard et al 2007;Datwani et al 2009;Glynn et al 2011;Washburn et al 2011;Bilousova et al 2012;Chacon and Boulanger 2013; for reviews, see Boulanger et al 2001;Boulanger and Shatz 2004;Boulanger 2009;McAllister and van de Water 2009;Shatz 2009;Elmer and McAllister 2012). MHC class I mRNA is highly expressed in sites of ongoing adult plasticity, including adult hippocampus (Corriveau et al 1998;Huh et al 2000), where it is present in dendrites of CA1 pyramidal neurons (Zhong et al 2006).…”
mentioning
confidence: 99%
“…However, a growing number of studies have identified unexpected, nonimmune roles for MHC class I in the brain (e.g. (Chacon and Boulanger, 2013;Datwani et al, 2009;Elmer et al, 2013;Glynn et al, 2011;Goddard et al, 2007;Huh et al, 2000;Lee et al, 2014;Leinders-Zufall et al, 2014;Loconto et al, 2003;McConnell et al, 2009;Needleman et al, 2010;Nelson et al, 2013;Washburn et al, 2011;Wu et al, 2010;Zohar et al, 2008)). …”
Section: Major Histocompatibility Complex (Mhc); Major Histocompatibimentioning
confidence: 99%
“…Experiments with MHC class I-deficient or -overexpressing neurons growing in vitro suggest that MHC class I limits axon outgrowth in retinal explants and cultured dorsal root ganglion neurons (Bilousova et al, 2012;Escande-Beillard et al, 2010;Washburn et al, 2011;Wu et al, 2011). Similarly, anti-MHC class I antibodies promote neurite outgrowth in cultured cortical neurons (Zohar et al, 2008).…”
Section: Mhc Class I Regulates Axonal and Dendritic Growthmentioning
confidence: 99%